Comparison of bupivacaine infiltration with and without tramadol for post-operative analgesia in split skin graft donor sites: A prospective randomized controlled study - Petkar, Kiran; Amrutha S (Asian Journal of Medical Sciences, 2025)
Background: Split skin graft (SSG) creates a new partial-thickness wound at the donor site. Donor site pain is the most common concern in the post-operative period. Local infiltration of the donor site is an effective way to reduce immediate post-operative pain. Prolonged pain relief is always sought after. Aims and Objectives: In this study, we intend to know if the addition of tramadol to bupivacaine local infiltration prolongs post-operative analgesia. Materials and Methods: Sixty patients posted for SSG with donor site in the thigh were included in the study. They were divided into Group BB, who received local infiltration of the donor site with 0.25% bupivacaine, and Group BT who received local infiltration with 0.25% bupivacaine and 50 mg tramadol. Visual analog scale (VAS) score up to 24 h, time of 1st rescue analgesia, total analgesic consumption in 24 h, and side effects were noted. Results: Patients in Group BB had significantly higher VAS scores at 8, 9, 10, 11,12, and 16 h as compared to Group BT. The time of first rescue analgesia was higher in Group BT with 721.03±54.79 min as compared to Group BT which had 463.21±43.89 min and these values were statistically significant. Total rescue analgesia consumption was significantly higher in Group BB with 2928.57±377.96 g when compared with Group BT which had 2068±257.88 g. There were no significant side effects. Conclusion: Local infiltration of the donor site with bupivacaine and tramadol combination decreased the post-operative pain score, total analgesic consumption, and prolonged the time of first rescue analgesia as compared to local infiltration of donor site with bupivacaine alone with minimum side effects.